THE EFFECT OF ORGANIZATIONAL CITIZENSHIP BEHAVIOR (OCB) AND JOB SATISFACTION ON EMPLOYEE PERFORMANCE AT CV. SABILLAH - Andi Elsa Marina; Djabir Hamzah; Muhammad Idrus Taba (Program Studi Akuntansi Universitas Kristen Indonesia Paulus, 2023)
Employee performance is the result of work carried out in quantity and quality in carrying out work that is the duty and responsibility of employees. The behavior and actions taken by an employee will affect the achievement of the organization. One example is the willingness of employees to voluntarily assist other employees, commonly known as the concept of Organizational Citizenship Behavior. In addition, jobsatisfaction is also related to the performance shown by employees. The more satisfied they are with their work, the employees will improve their performance. This study aims to analyze the influence of Organizational Citizenship Behavior (OCB) and job satisfaction on the employee performance of CV Sabillah Bone. The research method uses quantitative research with a descriptive design. Research begins in March-April 2023 at CV. Sabillah in Bone Regency, South Sulawesi. The number of samples used were 46 employees who were taken using the total sampling technique. Data collection was measured using a questionnaire with a Likert scale which was filled directly by the respondents. Data were analyzed using a hypothesis testing test that began with the F test (ANOVA), t test, and analysis of the Coefficient of Determination (R2). The test results show that Organizational Citizenship Behavior (OCB) and job satisfaction have a significant effect on employee performance. Therefore, employees must maintain an attitude of always caring to their work surroundings. This situation can be in the form of employee concern or sensitivity to co-workers.